The efficacy of GnRH agonist trigger followed by hCG add-back in normal responders for fresh embryo transfer: a case-control analysis from Vietnam - M.T. Le; N.S.V. Le; N.Q.T. Tran; Q.H.V. Nguyen; T.N. Cao (IRBIS LLC, 2023)
Aim: to assess the effects of a dual trigger by gonadotrophin-releasing hormone (GnRH) agonist and low-dose human chorionic gonadotropin (hCG) on in vitro fertilization (IVF) outcomes in women with normal ovarian response.Materials and Methods. This case-control analysis comprised 118 patients who responded normally to ovarian stimulation with a GnRH antagonist protocol at Hue Center for Reproductive Endocrinology and Infertility, Vietnam, between January 2018 and October 2019. Recruitment was achieved through case-control matching: a case (with Dual trigger - group A) was paired with control (with hCG trigger - group B) in a 1:1 ratio. The primary markers of success were the retrieval of oocytes and embryological data, the pregnancy rate, and the incidence of ovarian hyperstimulation syndrome (OHSS).Results. 59 patients in group A and 59 women in group B were recruited. Two groups had comparable patient characteristics and ovarian reserve. The initial dose, total dose, duration of gonadotropin administration, and peak of estradiol level were not statistically different across groups. The number of recovered oocytes (10.3 ± 4.2 vs. 10.0 ± 3.3; p = 0.663), mature oocytes (8.6 ± 3.7 vs.8.1 ± 2.8; p = 0.346), and high-quality embryos (56.2 ± 28.9 vs. 59.8 ± 35.9; p = 0.555) was equivalent. Fertilization, clinical pregnancy, and live birth rates were comparable between the dual trigger and hCG groups. In neither group were any occurrences of OHSS seen.Conclusion. Dual trigger may substitute hCG for final oocyte maturation and fresh embryo transfer in patients with normal responses to GnRH antagonist protocol-induced ovarian stimulation without compromising IVF outcomes.